Genetic determinants of variability in warfarin response after the dose-titration phase. Issue 11 (November 2016) - Iwuchukwu, Otito F.; Ramirez, Andrea H.; Shi, Yaping; Bowton, Erica A.; Kawai, Vivian K.; Schildcrout, Jonathan S.; Roden, Dan M.; Denny, Joshua C.; Stein, C. Michael
Abstract : Objectives: Genetic factors contribute considerably toward variability in warfarin dose requirements and are important in the dose-titration phase; their effects on the stability of anticoagulation later in therapy are not known. Methods: Using deidentified electronic medical records linked to a DNA-biobank, we studied 140 African-Americans and 943 European-Americans after the warfarin dose-titration phase. We genotyped 12 single nucleotide polymorphisms in genes ( CYP2C9, VKORC1, CYP4F2, GGCX, EPHX1, CALU ) associated with altered warfarin dose requirements and tested their associations with international normalized ratio variability (INRVAR ) and percent time in therapeutic range in European-Americans and African-Americans. Results: One allele copy of rs2108622 in CYP4F2 was associated with a 15% [95% confidence interval (CI): 1–26, P =0.03] decrease in the median INRVAR in European-Americans. In African-Americans, GGCX variants rs11676382 and rs699664 were associated with 4.16-fold (95% CI: 1.45–11.97, P =0.009) and 1.50-fold (95% CI: 1.07–2.08, P =0.02) changes in the median INRVAR per variant allele copy, respectively; rs11676382 was also significantly associated with a 23.19% (95% CI: 5.89–40.48, P =0.01) decrease in time in therapeutic range. The total variation in INRVAR explained by both clinical factors and rs2108622 was 5.2% for European-Americans. In African-Americans, the inclusion of GGCX variants rs11676382 and rs699664, and the CYP2C9*8 variant rs7900194 explained ∼29% of the variation in INRVAR . Conclusion: The stability of anticoagulation after the warfarin dose-titration phase is differentially affected by variants in CYP4F2 in European-Americans and GGCX loci in African-Americans. Abstract : Supplemental Digital Content is available in the text.